Gradient neodymium iron boron permanent magnet and preparation method thereof
By stacking sintered NdFeB permanent magnet sheets of different grades and forming an insulating adhesive layer, the demagnetization problem and high cost of sintered NdFeB permanent magnets in high temperature environments is solved, and a gradient NdFeB permanent magnet with high surface magnetism and anti-demagnetization capability is achieved.
Patent Information
- Application Number
- CN202510383016.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-28
- Publication Date
- 2025-06-27
AI Technical Summary
The eddy current loss of existing sintered NdFeB permanent magnets during high-speed rotation leads to an increase in temperature, which leads to demagnetization problems. At the same time, the large amount of rare earth elements will increase costs and reduce residual magnetism.
By stacking and bonding the sintered NdFeB permanent magnet sheets of different grades in coercive force high-low, coercive force high-low-high or phase-to-phase arrangement, a gradient NdFeB permanent magnet is formed, and pressurized and cured in vacuum to form an insulating bonding layer.
The surface magnetization and anti-demagnetization capability of neodymium iron boron permanent magnets is improved, production costs are reduced, production processes are simplified, and production efficiency is improved.
Smart Images

Figure CN120221208A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of neodymium iron boron permanent magnets, and particularly to a gradient neodymium iron boron permanent magnet and a preparation method thereof. Background Art
[0002] Sintered neodymium iron boron permanent magnets have excellent magnetic properties and are widely used in fields such as traditional automobiles, wind power generation, new energy vehicles, energy-saving household appliances, variable-frequency air conditioners, and medical devices. Eddy current losses generated when sintered neodymium iron boron permanent magnets rotate at high speeds will cause their temperature to rise, thereby causing the sintered neodymium iron boron permanent magnets to demagnetize. The magnetic loss of sintered neodymium iron boron permanent magnets has become a key factor for permanent magnet motors to operate normally in high-temperature environments.
[0003] As is well known, in sintered neodymium iron boron permanent magnets, a part of Nd in Nd2Fe 14 B is replaced by rare earth Dy and / or Tb elements to form a Dy2Fe 14 B and / or Tb2Fe 14 B main phase with high intrinsic magnetic properties, thereby enabling the sintered neodymium iron boron permanent magnet to have higher magnetic properties and demagnetization resistance. However, adding a large amount of rare earth Dy and / or Tb elements will cause the remanence to decrease. In addition, rare earth Dy and / or Tb elements are expensive, and using a large amount of rare earth Dy and / or Tb elements will result in too high a cost of the permanent magnet.
[0004] The use of the grain boundary diffusion method can improve the coercivity of sintered neodymium iron boron permanent magnets and suppress the decrease of remanence. However, during the diffusion process, due to the large size of the bulk sintered neodymium iron boron permanent magnet, the diffusion depth of rare earth Dy and / or Tb elements and their low-melting-point alloys and other low-melting-point alloys in the sintered neodymium iron boron permanent magnet and the number of (Nd, Dy / Tb)2Fe 14 B main phases with high intrinsic magnetic properties formed are very limited. In addition, the method of using the grain boundary diffusion method to improve the coercivity of sintered neodymium iron boron permanent magnets has a more complicated production process, a longer cycle, and a higher production cost. Due to the deficiencies of the existing technology, how to further improve the surface magnetism and demagnetization resistance of neodymium iron boron permanent magnets, improve production efficiency, and reduce costs is the content that researchers in this field pay special attention to and is also a difficulty.
[0005] CN107671497A discloses a production method of a neodymium iron boron component for an electric motor, including the following steps: After surface treatment of a required number of cuboid neodymium iron boron magnets with the same size, apply glue on the surface formed by the length and width, and sequentially bond the cuboid neodymium iron boron magnets in a fixture to form a neodymium iron boron magnet bonded body; Align the cuboid neodymium iron boron magnets in the bonded body, and compact the glued part. After the glued part is cured, perform multi-slice cutting on the bonded body in a direction perpendicular to the bonding surface to obtain multiple small-sized magnet components with the glued part already cured. Although this technology bonds multiple cuboid neodymium iron boron magnets through a bonding technique, it is not a bonding in the magnetization direction and fails to achieve a change in the magnetic properties of the bonded body.
[0006] CN109994309B discloses a bonding method of a neodymium iron boron magnet component. By forming an insulating layer on the surface of the neodymium iron boron magnet, then bonding the neodymium iron boron magnets with the insulating layer together through a bonding method, and adding glass beads with an average particle size D50 of 12 - 19 μm to the insulating layer to reduce eddy current loss, but the effect of reducing its turbine loss is limited, and it also fails to achieve a change in the magnetic properties of the neodymium iron boron magnet component.
[0007] CN104454852B discloses a method for insulating bonding of a permanent magnet neodymium iron boron magnetic steel, including process steps such as surface treatment of the permanent magnet neodymium iron boron magnetic steel, coating of an insulating adhesive, primary curing, secondary curing, and post-processing. This method forms an insulating glued layer by using a one-time coating and secondary curing process, unable to ensure the consistency of the insulating bonding layer, and also fails to achieve a change in the magnetic properties of the neodymium iron boron magnet component. Summary of the Invention
[0008] The purpose of the present invention is to overcome the deficiencies of the prior art and propose a gradient neodymium iron boron permanent magnet and its preparation method.
[0009] To achieve the above purpose, the specific technical solution adopted by the present invention is as follows:
[0010] A gradient neodymium iron boron permanent magnet is formed by stacking and bonding different grades of sintered neodymium iron boron permanent magnets in an arrangement of high coercivity - low coercivity, high coercivity - low coercivity - high coercivity, or alternating, and then sintering; The sintered neodymium iron boron permanent magnets used are different grades of sintered neodymium iron boron permanent magnets with R2Fe 14 B-type compound grains as the main phase, where R is one or more of the rare earth elements Nd, Pr, La, Ce, Y, Dy, Tb, Gd, Ho, Sm, Er. The sintered neodymium iron boron permanent magnets of the present invention can use different grades of commercial sintered neodymium iron boron permanent magnets conventional in the art, or can also use sintered neodymium iron boron permanent magnets prepared experimentally according to magnetic property requirements and not meeting national standards.
[0011] Furthermore, the present invention also provides a method for preparing the above-mentioned gradient neodymium-iron-boron permanent magnet, comprising the following steps:
[0012] S1. Cut and grind the sintered neodymium-iron-boron blanks of grades M1, M2, M3, …, M n into sintered neodymium-iron-boron permanent magnet thin sheets. The numbers of the sintered neodymium-iron-boron permanent magnet thin sheets are M1 ' , M2 ' , M3 ' , …, M n ' respectively;
[0013] S2. Clean or wash the dirt and impurities on the surfaces of the sintered neodymium-iron-boron permanent magnet thin sheets. Specifically, when operating, put the sintered neodymium-iron-boron permanent magnet thin sheets into an ultrasonic cleaner, take them out and dry them after cleaning for 10 - 30 min, and wipe them with organic solvents such as ethanol and petroleum ether until the surface powder particles, oil stains and grease are wiped clean;
[0014] S3. Coat the contact surfaces between the sintered neodymium-iron-boron permanent magnet thin sheets of grades M1, M2, M3, …, M n with an insulating adhesive, and form a stacked neodymium-iron-boron permanent magnet in the arrangement of high coercivity - low coercivity, high coercivity - low coercivity - high coercivity or alternating. Specifically, when operating, first lay the sintered neodymium-iron-boron permanent magnet thin sheets of grade M1 flat on the conveyor belt of a screen printing machine, and then brush a layer of insulating adhesive on the upper surface of the sintered neodymium-iron-boron permanent magnet thin sheets of grade M1. Then, lay the sintered neodymium-iron-boron permanent magnet thin sheets of grade M2 flat on the sintered neodymium-iron-boron permanent magnet thin sheets of grade M1, and then brush a layer of insulating adhesive on the upper surface of the sintered neodymium-iron-boron permanent magnet thin sheets of grade M2, and so on, until the sintered neodymium-iron-boron permanent magnet thin sheets of grade M n are laid flat on the sintered neodymium-iron-boron permanent magnet thin sheets of grade M n-1 to obtain a stacked neodymium-iron-boron permanent magnet;
[0015] S4. Apply a pressure of 0 - 1.00 MPa in the direction perpendicular to the bonding surface (magnetic orientation direction) of the stacked neodymium-iron-boron permanent magnet, and place it in an environment with a vacuum degree higher than 200 Pa and a temperature of 50 - 250 °C for curing for 30 - 300 min to obtain a neodymium-iron-boron permanent magnet with a magnetic property gradient.
[0016] In the method for preparing the gradient neodymium-iron-boron permanent magnet of the present invention, the numbers of the sintered neodymium-iron-boron permanent magnet thin sheets of grades M1, M2, M3, …, M n satisfy M1 ' ≤ M2 ' ≤ M2 ' ≤ … ≤ M n ' , and M1' +M2 ' +M2 ' +…+M n ' ≥2.
[0017] In the preparation method of the gradient NdFeB permanent magnet of the present invention, M1, M2, M3, …, M n The thickness h of the magnetic orientation direction of the sintered NdFeB permanent magnet thin sheet of the grade is between 0.03 and 20 mm, preferably between 0.1 and 15 mm, and h1 ≤ h2 ≤ h3 ≤ … ≤ h n .
[0018] In the preparation method of the gradient NdFeB permanent magnet of the present invention, the surface roughness Ra of the sintered NdFeB permanent magnet thin sheet is 0.2 to 12.5 μm. An appropriate surface roughness can enable the insulating adhesive to form a uniform insulating adhesive layer between the sintered NdFeB permanent magnet thin sheets.
[0019] In the preparation method of the gradient NdFeB permanent magnet of the present invention, M1, M2, M3, …, M n The coercivity of the sintered NdFeB permanent magnet thin sheet of the grade satisfies Hcj1 ≥ Hcj2 ≥ Hcj3 ≥ … ≥ Hcj n .
[0020] In the preparation method of the gradient NdFeB permanent magnet of the present invention, M1, M2, M3, …, M n The remanence of the sintered NdFeB permanent magnet thin sheet of the grade satisfies Br1 ≥ Br2 ≥ Br3 ≥ … ≥ Br n .
[0021] In the preparation method of the gradient NdFeB permanent magnet of the present invention, the viscosity of the insulating adhesive is 500 to 3000 mPa·s. An appropriate viscosity can enable the insulating adhesive to have good fluidity and adhesiveness, and uniformly adhere the insulating adhesive to the surface of the sintered NdFeB permanent magnet.
[0022] In the preparation method of the gradient NdFeB permanent magnet of the present invention, on the contact surface between the sintered NdFeB permanent magnet thin sheets of M1, M2, M3, …, M n grade, an insulating adhesive is coated by a screen printing machine, and the thickness of the insulating adhesive is 0.5 to 10 μm.
[0023] The present invention has the following characteristics and beneficial effects:
[0024] The surface magnetic field and the demagnetization resistance ability of the gradient NdFeB permanent magnet of the present invention are high, and the production efficiency is high and the cost is low.
[0025] The preparation process of the present invention is relatively simple, with low difficulty, can flexibly meet the magnetic property requirements, optimize the production process, and is conducive to obtaining a neodymium iron boron permanent magnet with a magnetic property gradient. Description of the Drawings
[0026] Figure 1 It is a bonding schematic diagram of a gradient neodymium iron boron permanent magnet according to Embodiment 1 of the present invention.
[0027] Figure 2 It is a bonding schematic diagram of a gradient neodymium iron boron permanent magnet according to Embodiment 2 of the present invention. Detailed Description of the Invention
[0028] The present invention will be described in detail below with reference to specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but do not limit the present invention in any form. It should be noted that, without conflict, the embodiments in the present invention and the features in the embodiments can be combined with each other.
[0029] In order to improve the surface magnetic field and demagnetization resistance of the neodymium iron boron permanent magnet, the present invention stacks and bonds multiple sintered neodymium iron boron permanent magnets of different grades in the order of high coercivity - low coercivity, high coercivity - low coercivity - high coercivity or alternating arrangement, and obtains a gradient neodymium iron boron permanent magnet through sintering. The temperature rise amplitude of this gradient neodymium iron boron permanent magnet is relatively small, so it can maintain high magnetic properties and ensure that the permanent magnet motor can operate normally in a high-temperature environment. In this embodiment, the sintered neodymium iron boron permanent magnet is a sintered neodymium iron boron permanent magnet of different grades with R2Fe 14 B-type compound grains as the main phase, where R is one or more of the rare earth elements Nd, Pr, La, Ce, Y, Dy, Tb, Gd, Ho, Sm, Er. The sintered neodymium iron boron permanent magnet can be a commercially available sintered neodymium iron boron permanent magnet of different grades in the art, or a sintered neodymium iron boron permanent magnet prepared experimentally according to magnetic property requirements and not meeting national standards.
[0030] The "residual magnetism" described in the present invention refers to the value of the magnetic induction intensity corresponding to the zero magnetic field strength on the saturation hysteresis loop, usually denoted as Br, with the unit of tesla (T) or gauss (Gs). 1 Gs = 0.0001 T.
[0031] The "coercivity" described in the present invention, also known as the intrinsic coercivity, refers to the magnetic field strength when the magnetic field is monotonically decreased to zero and then increased in the reverse direction from the saturated magnetization state of the magnet, so that the magnetization intensity decreases to zero along the saturation hysteresis loop, usually denoted as Hcj, with the unit of oersted (Oe) or ampere per meter (A / m). 1 Oe = 79.6 A / m.
[0032] The "surface magnetic induction" described in the present invention refers to the magnetic induction intensity on the surface of a magnet, which is defined as the magnetic flux passing through a unit area, so it is also called surface magnetic flux density, with the unit of tesla (T) or gauss (Gs). 1 Gs = 0.0001 T. The surface magnetic induction at different positions on the magnet surface is different. The "surface magnetic induction" mentioned here refers to the central surface magnetic induction of the surface perpendicular to the magnet orientation direction.
[0033] In the following embodiments, the involved test methods include:
[0034] Viscosity test of the insulating adhesive: Measured by a viscometer of model DV3T from Brookfield (shear rate 100 - 150 s -1 )
[0035] Determination of magnetic properties: Use a BH magnetometer to measure the magnetic properties of the sintered neodymium iron boron permanent magnet at room temperature to obtain the room temperature remanence and room temperature coercivity of the sintered neodymium iron boron permanent magnet.
[0036] Determination of surface magnetic induction: Use a gaussmeter to measure the surface magnetic induction intensity at the center of the surface perpendicular to the orientation direction of the sintered neodymium iron boron permanent magnet at room temperature to obtain the surface magnetic induction of the sintered neodymium iron boron permanent magnet.
[0037] Example 1
[0038] Refer to Figure 1 As shown, the neodymium iron boron permanent magnet with magnetic property gradient in the embodiment of the present invention includes a neodymium iron boron magnet and an insulating adhesive layer, and its preparation method includes the following steps:
[0039] (1) Cut and grind the sintered neodymium iron boron permanent magnets of grades M1, M2, and M3 into thin sheets with the thickness h of the magnetic orientation direction being 0.6 mm, 1.0 mm, and 4.4 mm respectively. Prepare one thin sheet of the sintered neodymium iron boron permanent magnets of grades M1, M2, and M3 respectively. Among them, the remanences of the sintered neodymium iron boron permanent magnets of grades M1, M2, and M3 are 14.21 kGs, 14.19 kGs, and 14.18 kGs respectively, and the coercivities are 21.07 kOe, 18.53 kOe, and 12.05 kOe respectively. The sintered neodymium iron boron permanent magnet of grade M1 is a sintered neodymium iron boron permanent magnet with grains of Nd2Fe 14 B and Tb2Fe 14 B type compounds as the main phase. The sintered neodymium iron boron permanent magnet of grade M2 is a sintered neodymium iron boron permanent magnet with grains of Pr2Fe 14 B, Nd2Fe 14 B and Sm2Fe 14 B type compounds as the main phase. The sintered neodymium iron boron permanent magnet of grade M3 is a sintered neodymium iron boron permanent magnet with grains of Pr2Fe 14 B, Nd2Fe 14 B, Ce2Fe 14B and Y2Fe 14 A sintered NdFeB permanent magnet with B-type compound grains as the main phase.
[0040] (2) Place the sintered NdFeB permanent magnet thin sheet into an ultrasonic cleaner, take it out and dry it after cleaning for 20 minutes, and wipe it with organic solvents such as ethanol and petroleum ether until the surface powder particles, oil stains and grease are wiped clean, and the surface roughness Ra is about 0.5μm respectively.
[0041] (3) Lay the sintered NdFeB permanent magnet thin sheet of grade M1 flat on the conveyor belt of the screen printing machine, and brush a layer of insulating adhesive on the upper surface of the sintered NdFeB permanent magnet thin sheet of grade M1. The viscosity of the insulating adhesive is about 1000mPa·s. Then, lay the sintered NdFeB permanent magnet thin sheet of grade M2 flat on the sintered NdFeB permanent magnet thin sheet of grade M1, and brush a layer of insulating adhesive on the upper surface of the sintered NdFeB permanent magnet thin sheet of grade M2 until the sintered NdFeB permanent magnet thin sheet of grade M3 is laid flat on the sintered NdFeB permanent magnet thin sheet of grade M2 to obtain a stacked NdFeB permanent magnet.
[0042] (4) Apply a pressure of 0.2MPa to the stacked NdFeB permanent magnet in the direction perpendicular to the bonding surface (along the magnetic orientation direction), and cure it for 120 minutes in an environment with a vacuum degree of 100Pa and a temperature of 200°C to form an insulating adhesive layer with a thickness of about 3μm, and obtain a NdFeB permanent magnet with magnetic property gradient;
[0043] Cut and grind the NdFeB permanent magnet with magnetic property gradient into the dimensions of the target product and test sample. Here, the test sample size is 10×10×6mm, and measure its remanence Br / kGs, coercivity Hcj / kOe and surface magnetic field B / kGs. The test results are shown in Table 1.
[0044] Comparative Example 1
[0045] Cut and grind the sintered NdFeB blank of grade M3 in Example 1 into a thin sheet of 10×10×6mm. The thickness h of the magnetic orientation direction is 6.0mm, and measure its remanence Br / kGs, coercivity Hcj / kOe and surface magnetic field B / kGs. The test results are shown in Table 1.
[0046] Example 2
[0047] Refer to Figure 2 As shown, the preparation method of the NdFeB permanent magnet with magnetic property gradient described in the embodiment of the present invention is as follows:
[0048] (1) The sintered NdFeB permanent magnets of grades M1, M2, and M3 are processed by cutting and grinding into thin sheets with a thickness h of the magnetic orientation direction of 0.5 mm, 0.5 mm, and 4.0 mm respectively. Two thin sheets of the sintered NdFeB permanent magnets of grades M1 and M2 and one thin sheet of the sintered NdFeB permanent magnet of grade M3 are prepared respectively. The remanences of the sintered NdFeB permanent magnets of grades M1, M2, and M3 are 14.21 kGs, 13.45 kGs, and 11.05 kGs respectively, and the coercivities are 20.38 kOe, 14.26 kOe, and 10.25 kOe respectively. The sintered NdFeB permanent magnet of grade M1 is a sintered NdFeB permanent magnet with grains of Nd2Fe 14 B and Dy2Fe 14 B type compounds as the main phase. The sintered NdFeB permanent magnet of grade M2 is a sintered NdFeB permanent magnet with grains of Pr2Fe 14 B, Nd2Fe 14 B, Gd2Fe 14 B, and Er2Fe 14 B type compounds as the main phase. The sintered NdFeB permanent magnet of grade M3 is a sintered NdFeB permanent magnet with grains of Pr2Fe 14 B, Nd2Fe 14 B, Ce2Fe 14 B, and La2Fe 14 B type compounds as the main phase.
[0049] (3) An insulating adhesive is coated on the contact surfaces between the thin sheets of the sintered NdFeB permanent magnets of grades M1, M2, and M3 to form a stacked NdFeB permanent magnet. During the operation, first, the thin sheet of the sintered NdFeB permanent magnet of grade M1 is laid flat on the conveyor belt of the screen printing machine, and then a layer of insulating adhesive with a viscosity of about 1000 mPa·s is brushed on the upper surface of the thin sheet of the sintered NdFeB permanent magnet of grade M1. Then, the thin sheet of the sintered NdFeB permanent magnet of grade M2 is laid flat on the thin sheet of the sintered NdFeB permanent magnet of grade M1, and then a layer of insulating adhesive is brushed on the upper surface of the thin sheet of the sintered NdFeB permanent magnet of grade M2. And the thin sheet of the sintered NdFeB permanent magnet of grade M3 is laid flat on the thin sheet of the sintered NdFeB permanent magnet of grade M2 until the bonding of the thin sheets of the sintered NdFeB permanent magnets of grades M2 and M1 is completed, obtaining a stacked NdFeB permanent magnet.
[0050] Steps (2) and (4) are the same as those in Example 1. Finally, the NdFeB permanent magnet with a magnetic property gradient is processed by cutting and grinding into the dimensions of the target product and test samples. Here, the size of the test sample is 10×10×6 mm, and its remanence Br / kGs, coercivity Hcj / kOe, and surface magnetic field B / kGs are measured. The test results are shown in Table 1.
[0051] Comparative Example 2
[0052] The sintered NdFeB blank of grade M3 in Example 2 was processed by cutting and grinding into a thin sheet of 10×10×6 mm, with the thickness h of the magnetic orientation direction being 6.0 mm, and its remanence Br / kGs, coercivity Hcj / kOe and surface magnetic field B / kGs were measured. The test results are shown in Table 1.
[0053] Table 1
[0054]
[0055] As can be seen from Table 1, compared with the sintered NdFeB permanent magnet in Comparative Example 1, the surface magnetic field and coercivity of the NdFeB permanent magnet with magnetic property gradient in Example 1 of the present invention increased significantly, and the remanence was similar. The coercivity gradient was realized inside the NdFeB permanent magnet in Example 1, and the surface magnetic fields at both ends were different in terms of magnetic orientation. Compared with the sintered NdFeB permanent magnet in Comparative Example 2, the surface magnetic field, coercivity and remanence of the NdFeB permanent magnet with magnetic property gradient in Example 2 of the present invention increased significantly. The coercivity and remanence gradients were realized inside the NdFeB permanent magnet in Example 2, and the surface magnetic fields at both ends were different in terms of magnetic orientation.
[0056] Example 3
[0057] Refer to Figure 1 As shown, the preparation method of the NdFeB permanent magnet with magnetic property gradient described in the embodiment of the present invention is as follows:
[0058] (1) The sintered NdFeB permanent magnets of grades M1, M2, and M3 were processed by cutting and grinding into thin sheets with the thickness h of the magnetic orientation direction being 1.0 mm, 1.0 mm, and 4.0 mm respectively. One thin sheet of each of the sintered NdFeB permanent magnets of grades M1, M2, and M3 was prepared. The remanences of the sintered NdFeB permanent magnets of grades M1, M2, and M3 were 14.85 kGs, 14.02 kGs, and 13.28 kGs respectively, and the coercivities were 12.32 kOe, 12.26 kOe, and 12.25 kOe respectively. The sintered NdFeB permanent magnet of grade M1 is a sintered NdFeB permanent magnet with Nd2Fe 14 B-type compound grains as the main phase, the sintered NdFeB permanent magnet of grade M2 is a sintered NdFeB permanent magnet with Pr2Fe 14 B, Nd2Fe 14 B, Ho2Fe 14 B, and Gd2Fe 14 B-type compound grains as the main phase, and the sintered NdFeB permanent magnet of grade M3 is a sintered NdFeB permanent magnet with Pr2Fe 14 B, Nd2Fe 14 B, Ce2Fe 14 B, and La2Fe 14 B-type compound grains as the main phase.
[0059] Steps (2) to (4) are the same as those in Example 1. Finally, the NdFeB permanent magnet with magnetic property gradient is cut and ground into the sizes of the target product and test samples. Here, the size of the test sample is 10×10×6 mm, and its remanence Br / kGs, coercivity Hcj / kOe and surface magnetic field B / kGs are measured. The test results are shown in Table 2.
[0060] Example 4
[0061] Referring to Figure 2 as shown, the preparation method of the NdFeB permanent magnet with magnetic property gradient of the present invention is as follows:
[0062] (1) Sintered NdFeB permanent magnets of grades M1, M2, and M3 are cut and ground into thin sheets with the thickness h of the magnetic orientation direction being 0.5 mm, 0.5 mm, and 4.0 mm respectively. Two thin sheets of sintered NdFeB permanent magnets of grades M1 and M2 and one thin sheet of sintered NdFeB permanent magnet of grade M3 are prepared respectively. The remanence and coercivity of the sintered NdFeB permanent magnets of grades M1, M2, and M3 are the same as those in Example 3.
[0063] Steps (2) to (4) are the same as those in Example 2. Finally, the NdFeB permanent magnet with magnetic property gradient is cut and ground into the sizes of the target product and test samples. Here, the size of the test sample is 10×10×6 mm, and its remanence Br / kGs, coercivity Hcj / kOe and surface magnetic field B / kGs are measured. The test results are shown in Table 2.
[0064] Comparative Example 3
[0065] The sintered NdFeB blank of grade M3 in Example 3 is cut and ground into a thin sheet of 10×10×6 mm, and the thickness h of the magnetic orientation direction is 6.0 mm. Its remanence Br / kGs, coercivity Hcj / kOe and surface magnetic field B / kGs are measured. The test results are shown in Table 2.
[0066] Table 2
[0067]
[0068] As can be seen from Table 2, compared with the sintered NdFeB permanent magnet in Comparative Example 3, the surface magnetic field and remanence of the NdFeB permanent magnets with magnetic property gradient in Examples 3 to 4 of the present invention increase significantly, and the coercivity is similar. In the NdFeB permanent magnet of Example 3, a remanence gradient is achieved inside, and the surface magnetic fields at both ends are different in terms of magnetic orientation. In the NdFeB permanent magnet of Example 4, a remanence gradient is achieved inside, and the surface magnetic fields at both ends are enhanced in terms of magnetic orientation.
[0069] The foregoing has shown and described the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and the descriptions in the specification are only preferred examples of the present invention, and are not used to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention will have various changes and improvements, and these changes and improvements all fall within the scope of the present invention claimed. The scope of the present invention claimed is defined by the appended claims and their equivalents.
Claims
1. A gradient NdFeB permanent magnet, characterized in that: The sintered NdFeB permanent magnets of different brands are stacked, bonded and sintered in a high-low coercivity, high-low-high coercivity or alternating arrangement; the sintered NdFeB permanent magnets are made of R2Fe 14 Different brands of sintered NdFeB permanent magnets with B-type compound grains as the main phase, wherein R is one or more of the rare earth elements Nd, Pr, La, Ce, Y, Dy, Tb, Gd, Ho, Sm, and Er.
2. The method for preparing a gradient NdFeB permanent magnet according to claim 1, characterized in that: The steps include: S1, M1, M2, M3, ..., M n The sintered NdFeB blanks of the brand are cut and grinded into sintered NdFeB permanent magnet sheets. The number of sintered NdFeB permanent magnet sheets is respectively M1 and M2. ' , M2 ' , M3 ' , …, M n ' ; S2. Clean or wash away the dirt and debris on the surface of the sintered NdFeB permanent magnet slice; S3, M1, M2, M3, ..., M n The contact surfaces between the sintered NdFeB permanent magnet sheets of different brands are coated with insulating adhesive to form stacked NdFeB permanent magnets in a high-low coercivity, high-low-high coercivity or alternating arrangement; S4. Apply pressure of 0 to 1.00 MPa in a direction perpendicular to the bonding surface of the stacked NdFeB permanent magnets, and place them in an environment with a vacuum degree higher than 200 Pa and a temperature of 50 to 250° C. for curing for 30 to 300 minutes to obtain NdFeB permanent magnets with a magnetic property gradient.
3. The method for preparing a gradient NdFeB permanent magnet according to claim 2, characterized in that: M1, M2, M3, ..., M n The number of sintered NdFeB permanent magnet sheets of the brand meets M1 ' ≤M2 ' ≤M2 ' ≤…≤M n ' , and M1 ' +M2 ' +M2 ' +…+M n ' ≥2.
4. The method for preparing a gradient NdFeB permanent magnet according to claim 2, characterized in that: M1, M2, M3, ..., M n The thickness h of the sintered NdFeB permanent magnet sheet in the magnetic orientation direction is between 0.1 and 15 mm, and h1≤h2≤h3≤…≤h n .
5. The method for preparing a gradient NdFeB permanent magnet according to claim 2, characterized in that: The surface roughness Ra of the sintered NdFeB permanent magnet slice is 0.2-12.5 μm.
6. The method for preparing a gradient NdFeB permanent magnet according to claim 2, characterized in that: M1, M2, M3, ..., M n The coercivity of the sintered NdFeB permanent magnet sheet of the brand meets Hcj1≥Hcj2≥Hcj3≥…≥Hcj n .
7. The method for preparing a gradient NdFeB permanent magnet according to claim 2, characterized in that: M1, M2, M3, ..., M n The remanence of the sintered NdFeB permanent magnet sheet of the brand meets Br1≥Br2≥Br3≥…≥Br n .
8. The method for preparing a gradient NdFeB permanent magnet according to claim 2, characterized in that: The viscosity of the insulating adhesive is 500 to 3000 mPa·s.
9. The method for preparing a gradient NdFeB permanent magnet according to claim 2, characterized in that: In M1, M2, M3, ..., M n The insulating adhesive is coated on the contact surface between the sintered NdFeB permanent magnet sheets of the brand by a screen printer, and the thickness of the insulating adhesive is 0.5 to 10 μm.
Citation Information
Patent Citations
Composite magnet manufacturing method using neodymium iron boron magnetic sheets
CN103839669A
Method for preparing composite NdFeB magnet with coercive gradient distribution characteristic
CN110136953A
Spliced neodymium-iron-boron magnet with gradient performance and preparation method thereof
CN116564691A
Sintered neodymium iron boron permanent magnet, rare earth permanent magnet and preparation method
CN117831879A
Composite multi-layer NdFeB magnet
CN201745223U